2D Surface potential and mobility modelling of doped/undoped symmetric double gate MOSFET. Issue 5 (28th June 2019) - Bose, Ria; Roy, J.N.
Abstract : The 2D surface potential and mobility models are proposed for symmetric doped/undoped channel double gate FET (DGFET) device. This is then used in drain current equation obtained by combining Pao‐Sah's double integral formula with Pierret–Shields' type current model. The surface potential model and mobility model both are analytic and differently solved for both undoped and doped device. Being an explicit and continuous expression, the drain current model is used to describe the behaviour of the device at below and above threshold condition. Simulations are carried out using TCAD Sentaurus bundle of Synopsis tool. The accuracy of the proposed model is analysed and compared with the simulation result for different channel length and channel thickness value of the device.